STRESS KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA BANK PANIN KOTA KENDARI - Kolewora, Riez Kifli; Nurhayati, Amy (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research aims to determine the influence of job stress and career development on employee performance at Bank Panin in Kendari City. The research is quantitative in nature, and data is obtained through questionnaires and documentation. The analysis method used is multiple linear regression analysis. This analysis is employed to measure the independent variables, namely job stress and career development, on the dependent variable, which is employee performance, with the assistance of SPSS 24 software. The number of respondents is 45 employees working at Bank Panin in Kendari. The results of this research indicate that job stress and career development simultaneously have an effect on employee performance. This is evidenced by the F-test result with a significance value smaller than the threshold significance value. Job stress, in partial terms, has a significant negative effect on employee performance, as indicated by the significance value smaller than the threshold significance value. On the other hand, career development, in partial terms, has a significant positive effect on employee performance, as indicated by the significance value smaller than the threshold significance value.